Frailty Among Older Adults With Acute Myocardial Infarction and Outcomes From Percutaneous Coronary Interventions - Damluji, Abdulla A.; Huang, Jin; Bandeen‐Roche, Karen; Forman, Daniel E.; Gerstenblith, Gary; Moscucci, Mauro; Resar, Jon R.; Varadhan, Ravi; Walston, Jeremy D.; Segal, Jodi B. (Journal of the American Heart Association, 2019)
Background Frailty is a predictor of adverse outcomes after acute myocardial infarction (AMI). Methods and Results We estimated the prevalence of frailty among adults age ≥75 years admitted with AMI and examined the relationship between frailty, interventions, and mortality. We used the Premier Healthcare Database to identify older adults with primary diagnoses of AMI. We classified individuals as frail or not using the validated Claims-based Frailty Index. We described patients' characteristics and receipt of percutaneous coronary intervention stratified by frailty status. The primary outcome was hospital mortality. From 2000 to 2016, we identified 469 390 encounters for older patients admitted with AMI. The median age was 82 years, 53% were women, and 75% were white. The prevalence of frailty was 19%. Frail patients were less likely to receive percutaneous coronary intervention than nonfrail (15% versus 33%, P<0.001) and much less likely to receive coronary artery bypass surgery (1% versus 9%, P<0.001). There were far fewer interventions in individuals over age 85 years. Frailty was associated with higher mortality during AMI admission (unadjusted odds ratio [OR] 1.43, CI 1.39-1.46). While there was a differential benefit of the interventions because of frailty, frail patients had reduced hospital mortality with percutaneous coronary intervention (frail: OR 0.59, CI 0.55-0.63; nonfrail: OR 0.49, CI 0.47-0.50, P for interaction <0.001) and with coronary artery bypass surgery (frail: OR 0.77, CI 0.65-0.93; nonfrail: OR 0.74, CI 0.71-0.77, P for interaction <0.001) relative to no intervention. Conclusions In the United States, frailty is common among older patients admitted with AMI. While these vulnerable patients are at an increased risk for mortality, judicial use of revascularization with percutaneous coronary intervention in frail older patients still confers immediate survival benefit.